The Magnetic Properties of Indonesian Lake Sediment: A Case Study of a Tectonic Lake in South Sulawesi and Maar Lakes in East Java - Gerald Tamuntuan; Satria Bijaksana; Edy Gaffar; James Russell; la Ode Safiuddin; Estavanus Huliselan (Institute for Research and Community Services (LPPM) ITB, 2010)
Magnetic properties of sediments from two different environmental settings in Indonesia have been studied using rock magnetic methods and scanning electron microscopy (SEM). In the first setting, magnetic measurements were conducted on core sediments from two maar lakes in East Java (Lakes Lading and Bedali) that represent very confined environments where sediments are derived mainly from rocks and soils within the craters. In the second setting, similar measurements were obtained on core sediment from Lake Matano, a cryptodepression lake in tectonically active South Sulawesi where the area around the lake is dominated by highly magnetic lateritic soils. The results show that the predominant magnetic mineralogy in sediments from Lakes Lading, Bedali, as well as Matano is pseudo-single domain (PSD) magnetite (Fe3O4). Compared to that of Lake Matano, the maar lake sediments of Lakes Lading and Bedali have higher magnetic susceptibility as well as high intensity of ARM and SIRM. Variations in magnetic susceptibility in all core sediments are controlled mainly by the concentration of magnetic minerals. The homogeneity of magnetic minerals in these three lakes sediment provides an excellent setting for interpreting paleoclimatic signals as they will be recorded as anomalies of magnetic susceptibility.